A TRAINING METHOD DEVELOPING LEARNERS’ COMPETENCE IN UNIVERSITIES - Nguyen Thi Thu Thuy (Journal of Applied Science and Technology, 2019)
Being well aware of the crucial importance of developing learners’ competence in education and training, our Communist Party and Government promulgated Decision 29-NQ/TW about comprehensive reform in education, claiming that training should shift from one-way knowledge transfer to developing learners’ competence and personalities. This must be reformed thoroughly in terms of curriculum, lesson activities and especially educators’ ways of thinking. This article aims at suggesting a training method developing learners’ competence in universities from the author’s viewpoints.